The Risk Factors of the Alcohol Use Disorders—Through Review of Its Comorbidities - Yang, Ping; Tao, Rui; He, Chengsen; Liu, Shen; Wang, Ying; Zhang, Xiaochu (Frontiers in Neuroscience, 2018)
Alcohol use disorders (AUDs) represent a severe, world-wide problem, and are usually comorbid with psychiatric disorders, comorbidity increases the risks associated with AUDs, and results in more serious consequences for patients. However, currently the underlying mechanisms of comorbid psychiatric disorders in AUDs are not clear. Studies investigating comorbidity could help us understand the neural mechanisms of AUDs. In this review, we explore three comorbidities in AUDs, including schizophrenia, major depressive disorder (MDD), and personality disorders (PDs). They are all co-morbidities of AUDs with rate of 33.7%, 28% and 50-70% respectively. The rate is significantly higher than other diseases. Therefore we review and analyze relevant literature to explore whether these three diseases are the risk factors of AUDs, focusing on studies assessing cognitive function and those using neural imaging. We found that memory deficits, impairment of cognitive control, negative emotion, and impulsivity may increase an individual’s vulnerability to AUDs. This comorbidity may indicate the neural basis of AUDs and reveal characteristics associated with different types of comorbidity, leading to further development of new treatment approaches for AUDs.